Analyzing the Intersection of Labor Market Dynamics and Economic Growth: A Bibliometric Study - Loso Judijanto; Supriyanto Supriyanto; Supriandi Supriandi (Westscience Press, 2024)
This study conducts a bibliometric analysis to examine the intersection of labor market dynamics and economic growth, focusing on key themes, trends, and emerging areas of research. Using VOSviewer, we analyze 980 publications from 1959 to 2024, identifying central themes such as